Promoting Local Tourism: Accessible Amenities and Travel Plans in East Nusa Tenggara After the Pandemic - Hapsari, Anggraeni Woro; Manoby, Worry Mambusy (E-Journal of Tourism, 2025)
The COVID-19 pandemic has wrought considerable effects on the tourism sector. Given this context, the main aim of this study is to apply the Theory of Planned Behavior (TPB) in a conceptual framework to elucidate the travel choices made by domestic tourists in the aftermath of the pandemic. The TPB, a well-established socio-psychological theory for forecasting human decision-making, serves as the basis for this research. By employing quantitative research methods, we have extended the TPB model to encompass tourists' awareness of inclusive amenities. This theoretical framework considers tourists' intentions to visit East Nusa Tenggara, a destination they view as comfortable and secure. The level of knowledge tourists have regarding inclusive facilities plays a pivotal role in improving the predictability of their intentions. The connection between subjective norms, attitudes, and intentions is substantially influenced by tourists' awareness of inclusive amenities. To sum up, the results of this study make a meaningful contribution to our understanding of how tourists make travel decisions in the post-pandemic period.